Catalytically Triggered Energy Release from Strained Organic Molecules: The Surface Chemistry of Quadricyclane and Norbornadiene on Pt(111). Issue 7 (29th December 2016) - Bauer, Udo; Mohr, Susanne; Döpper, Tibor; Bachmann, Philipp; Späth, Florian; Düll, Fabian; Schwarz, Matthias; Brummel, Olaf; Fromm, Lukas; Pinkert, Ute; Görling, Andreas; Hirsch, Andreas; et al.
Abstract: We have investigated the surface chemistry of the polycyclic valence‐isomer pair norbornadiene (NBD) and quadricyclane (QC) on Pt(111). The NBD/QC system is considered to be a prototype for energy storage in strained organic compounds. By using a multimethod approach, including UV photoelectron, high‐resolution X‐ray photoelectron, and IR reflection–absorption spectroscopic analysis and DFT calculations, we could unambiguously identify and differentiate between the two molecules in the multilayer phase, which implies that the energy‐loaded QC molecule is stable in this state. Upon adsorption in the (sub)monolayer regime, the different spectroscopies yielded identical spectra for NBD and QC at 125 and 160 K, when multilayer desorption takes place. This behavior is explained by a rapid cycloreversion of QC to NBD upon contact with the Pt surface. The NBD adsorbs in a η 2 :η 1 geometry with an agostic Pt−H interaction of the bridgehead CH2 subunit and the surface. Strong spectral changes are observed between 190 and 220 K because the hydrogen atom that forms the agostic bond is broke. This reaction yields a norbornadienyl intermediate species that is stable up to approximately 380 K. At higher temperatures, the molecule dehydrogenates and decomposes into smaller carbonaceous fragments. Abstract : A prototypical molecular‐energy storage system of norbornadiene (NBD) and quadricyclane (QC) was investigated by photoelectron and IR spectroscopic analysis supported by DFT calculations on Pt(111). Both compounds are clearly intact in physisorbed layers, whereas an immediate conversion from energy‐rich QC into energy‐lean NBD occurred, even at low temperature in the chemisorbed state when in direct contact with the surface. Furthermore, the adsorption geometry and the decomposition pathway of NBD are determined (see scheme).